Adhesive-free thermal laminate barrier heat seal film comprising polyethylene

By developing a laminate containing multilayer film and orientation film without laminated adhesive, the problem of difficulty in recycling existing laminates is solved, efficient thermal bonding and performance improvements are achieved, and the needs of sustainable and high-performance packaging are met.

CN115916524BActive Publication Date: 2025-03-04DOW GLOBAL TECHNOLOGIES LLC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202180039547.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-05
Filing Date
2021-04-26
Publication Date
2025-03-04
Estimated Expiration
2041-04-26

AI Technical Summary

Technical Problem

The existing laminates are difficult to recycle due to incompatibility between different materials and have insufficient performance to meet sustainable and high-performance packaging needs.

Method used

By providing a thermally bonded laminate without a laminated adhesive, the laminate comprising a multilayer film and a directional film consisting of an outer layer, a barrier layer, a sealant layer and an adhesive layer, the directional film is thermally laminated to the outer layer of the multilayer film and comprises an ethylene-based polymer having a density of 0.900 g/cm3 to 0.970 g/cm3.

Benefits of technology

The laminate achieves efficient thermal bonding without using an adhesive and is fully compatible in the polyethylene recirculation stream, showing performance characteristics comparable or better than conventional laminates, including bonding strength, oxygen transmittance, water vapor transfer rate, heat sealing properties, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003973226870000211
    Figure BDA0003973226870000211
  • Figure BDA0003973226870000221
    Figure BDA0003973226870000221
  • Figure BDA0003973226870000231
    Figure BDA0003973226870000231
Patent Text Reader

Abstract

The invention provides a heat-sealed barrier laminate comprising polyethylene. The laminate can be non-adhesive and fully compatible with polyethylene recycle streams. Compared to existing laminate structures that are fully compatible with polyethylene recycle streams, they can exhibit improved, continuous or desired properties. The laminate comprises a multilayer film and an oriented film. The oriented film is heat laminated to the outer layer of the multilayer film to provide the laminate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure relate generally to laminates, and more particularly to laminates comprising polyethylene. Background Art

[0002] Laminates incorporating polypropylene, polyamide and polyethylene terephthalate contain multiple layers and are widely used in the flexible packaging of consumer goods. For example, typical laminates for flexible packaging can include an outer printed substrate of biaxially oriented polypropylene (BOPP), a barrier layer of a metallized film, an adhesive layer of a solvent-based adhesive and a sealant layer of polyethylene. The combination of layers and materials can allow heat resistance, good printability, high barrier properties and sealing without shrinkage of wide sealed windows. However, since different types of materials cannot be recyclable and compatible with each other, such laminates may be difficult to (if not impossible) recycle together. As the demand for sustainable and recyclable materials continues to rise, there is still a strong demand for laminates that can be more easily recycled and show comparable or improved performance characteristics with existing structures. Summary of the invention

[0003] Embodiments of the present disclosure meet the aforementioned needs by providing laminates that are thermally bonded without a laminating adhesive and that are fully recyclable and compatible in polyethylene recycling streams. The performance of the laminates of the present invention can be better than or at least comparable to other laminates (e.g., laminates containing BOPP), and can, for example, allow faster packaging speeds to be used during manufacturing. In various aspects, the recyclable laminates can exhibit improved or maintained properties such as bond strength, oxygen transmittance (OTR), water vapor transmission rate (WVTR), heat seal initiation temperature (HSIT), heat seal strength, hot tack strength, hot tack initiation temperature, and / or shrinkage when compared to existing laminates.

[0004] A laminate is disclosed herein. In an embodiment, the laminate includes: (a) a multilayer film comprising: (1) an outer layer comprising at least one of an anhydride-modified ethylene acrylate copolymer, an anhydride-modified polyethylene, an anhydride-modified ethylene vinyl acetate, an ethylene-vinyl acetate copolymer, a polyethylene / vinyl acetate copolymer, a polyethylene / ethylene acrylic acid copolymer, a polyethylene / acrylate copolymer, or a polyethylene elastomer / plastomer; (2) a barrier layer comprising an ethylene vinyl alcohol copolymer; (3) a sealant layer, wherein the sealant layer comprises at least 70% by weight of a maximum peak melting temperature (T m ) a polymer having a temperature of 108° C. or less; and (4) a tie layer located between the barrier layer and the sealant layer; and (b) an oriented film thermally laminated to an outer layer of the multilayer film and comprising a density of 0.900 g / cm 3Up to 0.970g / cm 3 Ethylene-based polymers.

[0005] These and other embodiments are described in more detail in the Detailed Description. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Figure 1 is a graph of the heat seal strength of the comparative examples and embodiments of the present invention discussed below.

[0007] Figure 2 is a graph of the hot tack strengths of the comparative examples and inventive examples discussed below. DETAILED DESCRIPTION

[0008] Various aspects of the disclosed laminates are described in more detail below. The laminates can have a wide variety of applications, including, for example, bags, stand-up bags, pillow bags, big bags, pre-made packaging, pouches, etc. However, the present disclosure should not be construed as limiting the embodiments set forth below, as the present disclosure is an illustrative implementation of the embodiments described herein.

[0009] As used herein, the term "polymer" means a polymeric compound prepared by polymerizing monomers of the same or different types. The generic term polymer thus encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer) and the terms copolymer or interpolymer. Trace impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.

[0010] As used herein, the term "polyethylene" or "ethylene-based polymer" shall mean a polymer comprising a majority amount (>50 mol%) of units derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); ultra low density polyethylene (ULDPE); very low density polyethylene (VLDPE); single-site catalyzed linear low density polyethylene, including linear and substantially linear low density resins (m-LLDPE); ethylene-based plastomers (POPs) and ethylene-based elastomers (POEs); medium density polyethylene (MDPE); and high density polyethylene (HDPE). These polyethylene materials are generally known in the art; however, the following description may help understand the differences between some of these different polyethylene resins.

[0011] The term "LDPE" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is defined to mean that the polymer is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at a pressure above 14,500 psi (100 MPa) using a free radical initiator such as a peroxide (see, e.g., US 4,599,392, which is hereby incorporated by reference). The density of LDPE resins is typically 0.916 g / cm 3 Up to 0.935g / cm 3 within the range.

[0012] The term "LLDPE" includes both resins made using conventional Ziegler-Natta catalyst systems and chromium-based catalyst systems and single-site catalysts (including but not limited to substituted mono- or dicyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyvalent aryloxyether catalysts (commonly referred to as bisphenylphenoxy), and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE, and includes substantially linear ethylene polymers as further defined in U.S. Pat. No. 5,272,236, U.S. Pat. No. 5,278,272, U.S. Pat. No. 5,582,923, and U.S. Pat. No. 5,733,155; homogeneously branched linear ethylene polymer compositions, such as those in U.S. Pat. No. 3,645,992; heterogeneously branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698; and / or blends thereof (such as U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,733,155). 5,854,045). LLDPE can be made by gas phase, solution phase or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0013] The term "MDPE" refers to a polyethylene having a density of 0.926 g / cm 3 Up to 0.935g / cm 3 "MDPE" is typically produced using chromium or Ziegler-Natta catalysts or using single-site catalysts, including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyvalent catalysts aryloxyether catalysts (commonly referred to as bisphenylphenoxy), and typically has a molecular weight distribution ("MWD") greater than 2.5.

[0014] The term "HDPE" refers to a polyethylene having a density greater than about 0.935 g / cm 3 and at most about 0.980 g / cm 3The polyethylene is generally prepared using Ziegler-Natta catalysts, chromium catalysts or single-site catalysts (including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (commonly known as metallocenes), constrained geometry catalysts, phosphinimine catalysts and polyvalent catalysts aryloxyether catalysts (commonly known as bisphenylphenoxy).

[0015] The term "ULDPE" refers to a polyethylene with a density of 0.855 to 0.912 g / cm 3 ULDPE is a polyethylene generally prepared with a Ziegler-Natta catalyst, a chromium catalyst or a single-site catalyst (including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts and multivalent catalysts (commonly referred to as bisphenylphenoxy). ULDPE includes but is not limited to polyethylene (based on ethylene) plastomers and polyethylene (based on ethylene) elastomers.

[0016] As used herein, the term "polyethylene elastomer / plastomer" shall mean a polyethylene elastomer / plastomer comprising units derived from ethylene and units derived from at least one C3-C 10 A substantially linear or linear ethylene / α-olefin copolymer containing units of an α-olefin comonomer, or at least one C4-C8 α-olefin comonomer, or at least one C6-C8 α-olefin comonomer, and containing a homogeneous short chain branching distribution. The density of the polyethylene elastomer / plastomer is 0.865 g / cm 3 , or 0.870g / cm 3 , or 0.880g / cm 3 , or 0.890g / cm 3 Up to 0.900g / cm 3 , or 0.902g / cm 3 , or 0.904g / cm 3 , or 0.909g / cm 3 , or 0.910g / cm 3 Non-limiting examples of polyethylene elastomers / plastomers include AFFINITY TM Plastomers and elastomers (available from The Dow Chemical Company), EXACT TM Plastomer (available from ExxonMobil Chemical), Tafmer (available from Mitsui), Nexlene TM (available from SK Chemicals Co.) and Lucene TM (Available from LG Chem Ltd.).

[0017] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.

[0018] Laminated multilayer films

[0019] Laminates disclosed herein include multilayer films. The multilayer films according to the embodiments disclosed herein include an outer layer, a barrier layer, a sealant layer, and a tie layer. In another embodiment, in addition to the outer layer, the barrier layer, the sealant layer, and the tie layer, the multilayer film also includes a second tie layer.

[0020] Outer layer of multilayer film

[0021] The multilayer film of the laminate includes an outer layer.

[0022] In an embodiment, the outer layer of the multilayer film is laminated to the oriented film as described below, and can be positioned near or adjacent to the barrier layer comprising ethylene vinyl alcohol copolymer. In other embodiments, the second adhesive layer is placed between the outer layer and the barrier layer. In even other embodiments, an additional layer can be placed between the outer layer and the barrier layer.

[0023] According to embodiments disclosed herein, the outer layer of the multilayer film comprises at least one of an anhydride-modified ethylene acrylate copolymer, anhydride-modified polyethylene, anhydride-modified ethylene vinyl acetate, polyethylene / acrylic acid ethylene copolymer, ethylene-vinyl acetate copolymer, polyethylene / vinyl acetate copolymer, polyethylene / acrylate copolymer, or polyethylene elastomer / plastomer.

[0024] In embodiments where the outer layer comprises ethylene-vinyl acetate copolymer, the density of the ethylene-vinyl acetate copolymer may be 0.930 g / cm 3 Up to 0.980g / cm 3 This article discloses and includes 0.930g / cm 3 Up to 0.980g / cm 3 All individual values ​​and subranges of density; for example, the density of ethylene-vinyl acetate copolymer can be 0.930 g / cm3 Up to 0.980g / cm 3 , 0.935g / cm 3 Up to 0.970g / cm 3 , 0.935g / cm 3 Up to 0.950g / cm 3 , 0.935g / cm 3 Up to 0.945g / cm 3 or 0.940g / cm 3 Up to 0.945g / cm 3 within the range.

[0025] In an embodiment where the outer layer comprises ethylene-vinyl acetate copolymer, the melt index (I2) of the ethylene-vinyl acetate copolymer is from 0.1 g / 10 min to 500 g / 10 min, or from 0.2 g / 10 min to 400 g / 10 min, or from 0.5 g / 10 min to 100 g / 10 min, or from 0.1 g / 10 min to 30 g / 10 min, or from 0.1 g / 10 min to 10 g / 10 min.

[0026] In embodiments where the outer layer comprises an ethylene-vinyl acetate copolymer, the ethylene-vinyl acetate copolymer can have a vinyl acetate content of 5 wt % to 50 wt %, based on the total weight of the ethylene-vinyl acetate copolymer. All individual values ​​and subranges of 5 wt % to 50 wt % vinyl acetate content are disclosed and included herein. For example, in some embodiments, the ethylene-vinyl acetate copolymer can have a vinyl acetate content of 5 wt % to 10 wt %, 10 wt % to 30 wt %, or 30 wt % to 50 wt %, based on the total weight of the ethylene-vinyl acetate copolymer.

[0027] Examples of commercially available ethylene vinyl acetates that may be used in some embodiments include ELVAX, available from The Dow Chemical Company of Midland, Michigan. TM 470 (18 wt% vinyl acetate content).

[0028] In embodiments where the outer layer comprises a polyethylene / acrylate copolymer, the density of the polyethylene / acrylate copolymer may be 0.925 g / cm 3 Up to 0.955g / cm 3 This article discloses and includes 0.925g / cm 3 Up to 0.955g / cm 3 All individual values ​​and subranges of density; for example, the density of a polyethylene / acrylate copolymer may be 0.925 g / cm 3 Up to 0.955g / cm 3 、0.925g / cm3 Up to 0.945g / cm 3 、0.930g / cm 3 Up to 0.955g / cm 3 、0.930g / cm 3 Up to 0.945g / cm 3 , 0.935g / cm 3 Up to 0.955g / cm 3 or 0.935g / cm 3 Up to 0.945g / cm 3 within the range.

[0029] In embodiments where the outer layer comprises a polyethylene / acrylate copolymer, the polyethylene / acrylate copolymer melt index (I2) may be from 0.1 g / 10 min to 50 g / 10 min, or from 0.5 g / 10 min to 20 g / 10 min, or from 1.0 g / 10 min to 10 g / 10 min.

[0030] Commercially available examples of polyethylene / acrylate copolymers that can be used in the outer layer include those available from The Dow Chemical Company, Midland, Michigan, under the name BYNEL TM Those commercially available include, for example, BYNEL TM 22E780 adhesive resin and BYNEL TM 22E757 adhesive resin.

[0031] In embodiments where the outer layer comprises a polyethylene elastomer / plastomer, the density of the polyethylene elastomer / plastomer may be 0.865 g / cm 3 Up to 0.910g / cm 3 This article discloses and includes 0.865g / cm 3 Up to 0.910g / cm 3 All individual values ​​and subranges of density; for example, the density of a polyethylene elastomer / plastomer can be 0.865 g / cm 3 Up to 0.910g / cm 3 , 0.865g / cm 3 Up to 0.900g / cm 3 , 0.865g / cm 3 Up to 0.890g / cm 3 , 0.865g / cm 3 Up to 0.880g / cm 3 、0.870g / cm 3 Up to 0.910g / cm 3 、0.870g / cm 3 Up to 0.900g / cm 3、0.870g / cm 3 Up to 0.890g / cm 3 、0.870g / cm 3 Up to 0.880g / cm 3 、0.880g / cm 3 Up to 0.910g / cm 3 、0.880g / cm 3 Up to 0.900g / cm 3 、0.880g / cm 3 Up to 0.890g / cm 3 、0.890g / cm 3 Up to 0.910g / cm 3 、0.890g / cm 3 Up to 0.900g / cm 3 or 0.900g / cm 3 Up to 0.910g / cm 3 within the range.

[0032] In the embodiment that the outer layer comprises polyethylene elastomer / plastomer, the melt index (I2) of polyethylene elastomer / plastomer is in the range of 0.50g / 10 minutes to 20g / 10 minutes (g / 10min). All individual values ​​and subranges of the melt index of 0.50g / 10min to 20g / 10min are disclosed and included herein; For example, the melt index of polyethylene elastomer / plastomer can be from upper limit 0.50g / 10min, 1.0g / 10min, 2.0g / 10min, 5.0g / 10min, 10.0g / 10min, 15g / 10min or 18g / 10min to lower limit 1.0g / 10min, 2.0g / 10min, 5.0g / 10min, 10.0g / 10min, 15g / 10min, 18g / 10min, 19g / 10min or 20g / 10min.

[0033] Commercially available examples of polyethylene elastomers / plastomers that can be used for the outer layer include those available from The Dow Chemical Company (Midland, Michigan) under the name AFFINITY TM Those commercially available include, for example, AFFINITY TM VP 8770G1、AFFINITY TM PF7266、AFFINITY TM PL 1881G and AFFINITY TM PF1140G.

[0034] In an embodiment, the outer layer further comprises at least one of a linear low density polyethylene, a low density polyethylene, a medium density polyethylene, or a high density polyethylene. In such embodiments, the outer layer may comprise at most 50 wt % of at least one of a linear low density polyethylene, a low density polyethylene, a medium density polyethylene, or a high density polyethylene.

[0035] Barrier layer of multilayer film

[0036] The multilayer film of the laminate includes a barrier layer.

[0037] In embodiments, the barrier layer of the multilayer film may be positioned adjacent to or proximate to the tie layer described below and the outer layers described above.The barrier layer according to embodiments disclosed herein comprises ethylene vinyl alcohol copolymer (EVOH).

[0038] In an embodiment, the ethylene content of the EVOH of the barrier layer is 20mol% to 50mol%. All sub-ranges and individual values ​​of the ethylene content of 20mol% to 50mol% are disclosed herein. For example, in an embodiment, the ethylene content of the EVOH of the barrier layer is 20mol% to 50mol%, or 22mol% to 45mol%, or 25mol% to 40mol%. It will be understood by those of ordinary skill in the art that the ethylene content of EVOH can contribute to the lower and higher OTR of the laminate disclosed herein (i.e., generally, the lower the ethylene content, the lower the OTR value that can be achieved). It will also be understood by those of ordinary skill in the art that a barrier layer comprising EVOH with a lower ethylene content can be suitable for flexible bottles and tube applications, and a barrier layer comprising EVOH with a higher ethylene content can allow for easier handling, long-term operational stability, and packaging types that require flexibility (flexible crack resistance), such as thermoformability.

[0039] Commercially available examples of EVOH that can be used for the barrier layer include EVAL® from Kuraray Co., Ltd. (Tokyo, Japan) under the name EVAL TM Those commercially available include, for example, EVAL TM H171B (38 mol% ethylene content) and EVAL TM F171b (32 mol% ethylene content).

[0040] Various thicknesses are contemplated for the multilayer film. In embodiments, the barrier layer is from 5% to 25% of the total thickness of the multilayer film.

[0041] Sealant layer of multilayer film

[0042] The multi-layer film of the laminate includes a sealant layer.

[0043] The sealant layer of the multilayer film comprises at least 70% by weight of the highest peak melting temperature (T m ) is a polymer with a temperature of 108°C or less. The sealant layer can serve as the inner surface of the laminate and can, for example, provide a means for sealing a package around a packaged product. The composition of the sealant layer may affect the ability of the laminate and the sealant layer to obtain a high seal bond strength at a lower sealing temperature. In an embodiment, the sealant layer is at least 10 microns thick. In a further embodiment, the sealant layer is 25% to 60% of the total thickness of the multilayer film.

[0044] The sealant layer of the multilayer film comprises at least 70% by weight of a polymer, based on the gross weight of the sealant layer. All individual values ​​and subranges of at least 70% by weight are disclosed and included herein. For example, in an embodiment, the sealant layer may comprise at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 99% by weight, at least 99.5% by weight, or 70% to 100% by weight, 75% to 99% by weight, 80% to 95% by weight, or 90% to 95% by weight of a polymer, based on the gross weight of the sealant layer.

[0045] The sealant layer of the multilayer film comprises at least 70% by weight of the highest peak melting temperature (T m ) is 108°C or less. All individual values ​​and subranges of 108°C or less are disclosed and included herein. For example, in an embodiment, the highest peak melting temperature (T m ) is 108°C or less, 106°C or less, 104°C or less, 102°C or less, 100°C or less, 98°C or less, 96°C or less, 94°C or less, or 92°C or less, or 70°C to 108°C, 70°C to 100°C, 70°C to 95°C, 75°C to 108°C, 75°C to 100°C, or 75°C to 95°C, wherein the highest peak melting temperature (T m ) can be measured according to the DSC test method described below.

[0046] In an embodiment, the polymer of the sealant layer comprises a maximum peak melting temperature (T m ) is 108° C. or less. In such embodiments, the density of the polyethylene elastomer / plastomer of the sealant layer may be 0.865 g / cm 3 Up to 0.910g / cm 3 This article discloses and includes 0.865g / cm 3 Up to 0.910g / cm 3 All individual values ​​and subranges of density; for example, the density of a polyethylene elastomer / plastomer can be 0.865 g / cm 3Up to 0.910g / cm 3 , 0.865g / cm 3 Up to 0.900g / cm 3 , 0.865g / cm 3 Up to 0.890g / cm 3 , 0.865g / cm 3 Up to 0.880g / cm 3 , 0.865g / cm 3 Up to 0.870g / cm 3 、0.870g / cm 3 Up to 0.910g / cm 3 、0.870g / cm 3 Up to 0.900g / cm 3 、0.870g / cm 3 Up to 0.890g / cm 3 、0.870g / cm 3 Up to 0.880g / cm 3 、0.880g / cm 3 Up to 0.910g / cm 3 、0.880g / cm 3 Up to 0.900g / cm 3 、0.880g / cm 3 Up to 0.890g / cm 3 、0.890g / cm 3 Up to 0.910g / cm 3 、0.890g / cm 3 Up to 0.900g / cm 3 or 0.900g / cm 3 Up to 0.910g / cm 3 within the range.

[0047] In embodiments where the polymer of the sealant layer comprises or consists of a polyethylene elastomer / plastomer, the melt index (I2) of the polyethylene elastomer / plastomer may be in the range of 0.50 g / 10 minutes to 20 g / 10 minutes (g / 10 min). All individual values ​​and subranges of melt indexes from 0.50 g / 10 min to 20 g / 10 min are disclosed herein and include; for example, the melt index of the polyethylene elastomer / plastomer may be from an upper limit of 0.50 g / 10 min, 1.0 g / 10 min, 2.0 g / 10 min, 5.0 g / 10 min, 10.0 g / 10 min, 15 g / 10 min, or 18 g / 10 min to a lower limit of 1.0 g / 10 min, 2.0 g / 10 min, 5.0 g / 10 min, 10.0 g / 10 min, 15 g / 10 min, 18 g / 10 min, 19 g / 10 min, or 20 g / 10 min.

[0048] Commercially available examples of polyethylene elastomers / plastomers that can be used in the sealant layer include those available from The Dow Chemical Company (Midland, Michigan) under the name AFFINITY TM Commercially available ones include, for example, AFFINITY TM VP8770G1、AFFINITY TM PF7266、AFFINITY TM PL 1881G and AFFINITY TM PF1140G.

[0049] In an embodiment, the polymer of the sealant layer comprises a maximum peak melting temperature (T m ) is 108 ° C or less ionomer of ethylene (meth) acrylic acid copolymer (also referred to herein as "ethylene acid copolymer ionomer") or consists of it. The cation source of the ionomer of ethylene acid copolymer can be a monovalent cation source or a divalent cation source, including formate, acetate, hydroxide, nitrate, carbonate and bicarbonate. In an embodiment, the ionomer of ethylene acid copolymer may be treated with one or more cations or cation sources, and the cations or cation sources may include magnesium, sodium, zinc or a combination thereof.

[0050] In an embodiment, the ethylene content of the ionomer of the ethylene acid copolymer is greater than 50 wt % or greater than 60 wt %, based on the total weight of the ionomer of the ethylene acid copolymer. For example, the ethylene content of the ionomer of the ethylene acid copolymer can be 50 wt % to 95 wt %, 50 wt % to 90 wt %, 50 wt % to 85 wt %, or 60 wt % to 80 wt %, based on the total weight of the ionomer of the ethylene acid copolymer.

[0051] In an embodiment, the melt index (I2) of the ionomer of ethylene acid copolymer is from 0.1 g / 10min to 16 g / 10min, from 0.5 g / 10min to 15 g / 10min, from 3 g / 10min to 13 g / 10min, from 3.5 g / 10min to 10 g / 10min, or from 5 g / 10min to 8 g / 10min. Commercially available ionomers of ethylene acid copolymer include those sold under the name SURLYN TM Those commercially available from The Dow Chemical Company (Midland, Michigan).

[0052] In an embodiment, the polymer of the sealant layer comprises a maximum peak melting temperature (T m ) is 108°C or less polyethylene or consists thereof. For example, in an embodiment, the polymer of the sealant layer may comprise or consist of a linear low density polyethylene (LLDPE). The density of the linear low density polyethylene may be less than or equal to 0.930 g / cm 3 . This article includes and discloses less than or equal to 0.930 g / cm 3 All individual values ​​and subranges of; for example, the density of linear low-density polyethylene can be from the lower limit of 0.870 g / cm 3 Up to 0.928g / cm 3 、0.925g / cm 3 , 0.920g / cm 3 or 0.915g / cm 3 0.870 g / cm is included and disclosed herein. 3 and 0.930g / cm 3 All individual values ​​and subranges in between.

[0053] Commercially available examples of polyethylene that can be used for the sealant layer include those available from The Dow Chemical Company under the name ELITE TM Those commercially available from AT include, for example, ELITE TM AT 6202 and ELITE TM AT 6410.

[0054] Except for at least 70% by weight of the highest peak melting temperature (T m) is 108° C. or less, in embodiments, the sealant layer may further include at least one additional polymer and / or at least one additive. For example, the at least one additional polymer may be selected from the group consisting of polyethylene, ethylene vinyl acetate, ethylene acrylic acid, or a combination thereof, in an amount less than 30% by weight of the sealant layer. And for example, the at least one additive may be selected from the group consisting of an antioxidant, a UV stabilizer, a heat stabilizer, a slip agent, an antiblocking agent, an antistatic agent, a pigment or colorant, a processing aid, a crosslinking catalyst, a flame retardant, a filler, a foaming agent, or a combination thereof, in an amount less than 30% by weight of the sealant layer.

[0055] Adhesive layer for multi-layer films

[0056] The multilayer film includes a tie layer between the barrier layer and the sealant layer. The tie layer can adhere the barrier layer to the sealant layer.

[0057] In an embodiment, the tie layer comprises an adhesive resin selected from an anhydride grafted ethylene-based polymer, an ethylene acid copolymer, and ethylene vinyl acetate. Examples of anhydride grafted moieties may include, but are not limited to, maleic anhydride, citraconic anhydride, 2-methylmaleic anhydride, 2-chloromaleic anhydride, 2,3-dimethylmaleic anhydride, bicyclo[2,2,1]-5-heptene-2,3-dicarboxylic anhydride and 4-methyl-4-cyclohexene-1,2-dicarboxylic anhydride, bicyclo(2.2.2)oct-5-ene-2,3-dicarboxylic anhydride, o-octahydronaphthalene-2,3-dicarboxylic anhydride. Anhydride, 2-oxa-1,3-diketospiro(4.4)non-7-ene, bicyclo(2.2.1)hept-5-ene-2,3-dicarboxylic anhydride, tetrahydrophthalic anhydride, norbornyl-5-ene-2,3-dicarboxylic anhydride, nadic anhydride, methylnadic anhydride, nadic anhydride, methylnadic anhydride, and x-methyl-bicyclo(2.2.1)hept-5-ene-2,3-dicarboxylic anhydride. In one embodiment, the anhydride grafted portion comprises maleic anhydride.

[0058] In an embodiment, the tie layer comprises an anhydride-modified linear low-density polyethylene. In an embodiment, the density of the anhydride-modified linear low-density polyethylene is 0.860 g / cm 3 Up to 0.935g / cm 3 This article discloses and includes 0.860g / cm 3 Up to 0.935g / cm 3 All individual values ​​and subranges of; for example, the density of anhydride-modified linear low-density polyethylene can be 0.875 g / cm 3 Up to 0.935g / cm 3 , 0.900g / cm 3 Up to 0.925g / cm 3 、0.910g / cm3 Up to 0.935g / cm 3 、0.910g / cm 3 Up to 0.925g / cm 3 、0.915g / cm 3 Up to 0.935g / cm 3 or 0.920g / cm 3 Up to 0.930g / cm 3 In an embodiment, the melt index (I2) of the anhydride-modified linear low density polyethylene is from 0.1 g / 10 min to 50 g / 10 min, or from 0.5 g / 10 min to 20 g / 10 min, or from 1.0 g / 10 min to 10 g / 10 min.

[0059] In an embodiment, based on the gross weight of the bonding layer, the bonding layer comprises an anhydride-modified linear low density polyethylene of 0 to 100 % by weight. All individual values ​​and subranges of 0 % by weight to 100 % by weight are disclosed and included herein. For example, in an embodiment, based on the gross weight of the bonding layer, the bonding layer can comprise an anhydride-modified linear low density polyethylene of 10 % by weight to 90 % by weight, 20 % by weight to 80 % by weight, 30 % by weight to 70 % by weight or 40 % by weight to 60 % by weight.

[0060] Examples of commercially available anhydride-modified linear low density polyethylenes that may be used in embodiments include BYNEL ® , commercially available from The Dow Chemical Company, Midland, Michigan. TM Series 4100 resins, such as BYNEL TM 41E710 and BYNEL TM 41E687.

[0061] In an embodiment, the bonding layer further comprises at least one of linear low density polyethylene, low density polyethylene, medium density polyethylene or high density polyethylene. For example, in an embodiment, the bonding layer further comprises a density of 0.945 g / cm 3 Up to 0.970g / cm 3 High density polyethylene within the range. This article discloses and includes 0.945g / cm 3 Up to 0.970g / cm 3 All individual values ​​and subranges of; for example, the density of high-density polyethylene can be 0.945 g / cm 3 Up to 0.965g / cm 3 、0.950g / cm 3 Up to 0.970g / cm 3 、0.950g / cm 3 Up to 0.965g / cm 3 , 0.955g / cm3 Up to 0.970g / cm 3 , 0.955g / cm 3 Up to 0.965g / cm 3 or 0.955g / cm 3 Up to 0.965g / cm 3 within the range.

[0062] In embodiments where high density polyethylene is present, the high density polyethylene of the tie layer may be ethylene and C3-C 12 The copolymer of comonomer. In an embodiment, based on the gross weight of the bonding layer, the bonding layer also comprises 0 wt % to 90 wt % of high density polyethylene. All individual values ​​and subranges of 0 wt % to 90 wt % are disclosed and included herein. For example, in an embodiment, based on the gross weight of the bonding layer, the bonding layer can comprise 10 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt % or 40 wt % to 60 wt % of high density polyethylene. In an embodiment, the melt index (I2) of the high density polyethylene can be 0.3 g / 10 min to 10.0 g / 10 min, 0.3 g / 10 min to 7.0 g / 10 min, 0.3 g / 10 min to 5.0 g / 10 min, 0.3 g / 10 min to 4.0 g / 10 min, 0.3 g / 10 min to 3.0 g / 10 min, 0.3 g / 10 min to 2.0 g / 10 min, or 0.3 g / 10 min to 1.5 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min.

[0063] Commercially available examples of high density polyethylene that can be used for the tie layer include those available from The Dow Chemical Company (Midland, Michigan) under the name ELITE TM 5960G1 and DOWLEX TM 2006G those commercially available.

[0064] Second tie layer for multilayer films

[0065] In an embodiment, the multilayer film further comprises a second tie layer between the outer layer and the barrier layer. The second tie layer can adhere the outer layer to the barrier layer.

[0066] In an embodiment, the second adhesive layer comprises an adhesive resin selected from an anhydride grafted ethylene-based polymer, an ethylene acid copolymer and ethylene vinyl acetate. Examples of anhydride grafted moieties may include, but are not limited to, maleic anhydride, citraconic anhydride, 2-methylmaleic anhydride, 2-chloromaleic anhydride, 2,3-dimethylmaleic anhydride, bicyclo[2,2,1]-5-heptene-2,3-dicarboxylic anhydride and 4-methyl-4-cyclohexene-1,2-dicarboxylic anhydride, bicyclo(2.2.2)oct-5-ene-2,3-dicarboxylic anhydride, o-octahydronaphthalene-2,3-dicarboxylic anhydride. Anhydride, 2-oxa-1,3-diketospiro(4.4)non-7-ene, bicyclo(2.2.1)hept-5-ene-2,3-dicarboxylic anhydride, tetrahydrophthalic anhydride, norbornyl-5-ene-2,3-dicarboxylic anhydride, nadic anhydride, methylnadic anhydride, nadic anhydride, methylnadic anhydride, and x-methyl-bicyclo(2.2.1)hept-5-ene-2,3-dicarboxylic anhydride. In one embodiment, the anhydride grafted portion comprises maleic anhydride.

[0067] In an embodiment, the second tie layer comprises an anhydride-modified linear low-density polyethylene. In an embodiment, the density of the anhydride-modified linear low-density polyethylene is between 0.860 g / cm 3 Up to 0.935g / cm 3 This article discloses and includes 0.860g / cm 3 Up to 0.935g / cm 3 All individual values ​​and subranges of; for example, the density of anhydride-modified linear low-density polyethylene can be 0.875 g / cm 3 Up to 0.935g / cm 3 , 0.900g / cm 3 Up to 0.925g / cm 3 、0.910g / cm 3 Up to 0.935g / cm 3 、0.910g / cm 3 Up to 0.925g / cm 3 、0.915g / cm 3 Up to 0.935g / cm 3 or 0.920g / cm 3 Up to 0.930g / cm 3 In an embodiment, the melt index (I2) of the anhydride-modified linear low density polyethylene is from 0.1 g / 10 min to 50 g / 10 min, or from 0.5 g / 10 min to 20 g / 10 min, or from 1.0 g / 10 min to 10 g / 10 min.

[0068] In an embodiment, based on the gross weight of the second bonding layer, the second bonding layer comprises an anhydride-modified linear low density polyethylene of 0 wt % to 100 wt %. All individual values ​​and subranges of 0 wt % to 100 wt % are disclosed and included herein. For example, in an embodiment, based on the gross weight of the second bonding layer, the second bonding layer can comprise an anhydride-modified linear low density polyethylene of 10 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt % or 40 wt % to 60 wt %.

[0069] Examples of commercially available anhydride-modified linear low density polyethylenes that may be used in embodiments include BYNEL ® , commercially available from The Dow Chemical Company, Midland, Michigan. TM Series 4100 resins, such as BYNEL TM 41E710 and BYNEL TM 41E687.

[0070] In an embodiment, the second adhesive layer further comprises at least one of linear low density polyethylene, low density polyethylene, medium density polyethylene or high density polyethylene. For example, in an embodiment, the second adhesive layer further comprises a density of 0.945 g / cm 3 Up to 0.970g / cm 3 High density polyethylene within the range. This article discloses and includes 0.945g / cm 3 Up to 0.970g / cm 3 For example, the density of the high-density polyethylene of the second bonding layer can be 0.945 g / cm 3 Up to 0.965g / cm 3 、0.950g / cm 3 Up to 0.970g / cm 3 、0.950g / cm 3 Up to 0.965g / cm 3 , 0.955g / cm 3 Up to 0.970g / cm 3 , 0.955g / cm 3 Up to 0.965g / cm 3 or 0.955g / cm 3 Up to 0.965g / cm 3 within the range.

[0071] In embodiments where high density polyethylene is present, the high density polyethylene of the second tie layer may be ethylene and C3-C 12The second adhesive layer may be a copolymer of a comonomer. In an embodiment, based on the gross weight of the second adhesive layer, the second adhesive layer comprises 0 wt % to 90 wt % of a high density polyethylene. All individual values ​​and subranges of 0 wt % to 90 wt % are disclosed and included herein. For example, in an embodiment, based on the gross weight of the second adhesive layer, the second adhesive layer may comprise 10 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt % or 40 wt % to 60 wt % of a high density polyethylene. In an embodiment, the melt index (I2) of the high-density polyethylene of the second bonding layer can be 0.3 g / 10min to 10.0 g / 10min, 0.3 g / 10min to 7.0 g / 10min, 0.3 g / 10min to 5.0 g / 10min, 0.3 g / 10min to 4.0 g / 10min, 0.3 g / 10min to 3.0 g / 10min, 0.3 g / 10min to 2.0 g / 10min, or 0.3 g / 10min to 1.5 g / 10min, or 0.5 g / 10min to 1.0 g / 10min.

[0072] Commercially available examples of high density polyethylene that can be used for the second tie layer include those available from The Dow Chemical Company, Midland, Michigan, under the name ELITE TM 5960G1 and DOWLEX TM 2006G those commercially available.

[0073] Oriented films for laminates

[0074] The laminates disclosed herein include oriented films. The oriented films according to the embodiments disclosed herein are heat laminated to the outer layers of the multilayer film and include a density of 0.900 g / cm 3 Up to 0.970g / cm 3 Ethylene-based polymers.

[0075] In an embodiment, the density of the ethylene-based polymer of the oriented film is 0.900 g / cm 3 Up to 0.970g / cm 3 . This article discloses and includes 0.900g / cm 3 Up to 0.970g / cm 3 For example, the density of an ethylene-based polymer may be 0.900 g / cm 3 Up to 0.970g / cm 3 、0.910g / cm 3 Up to 0.957g / cm 3 , 0.920g / cm 3 Up to 0.947g / cm 3 , 0.920g / cm3 Up to 0.937g / cm 3 , 0.920g / cm 3 Up to 0.930g / cm 3 or 0.920g / cm 3 Up to 0.927g / cm 3 .

[0076] In an embodiment, the ethylene-based polymer has a melt index (I2) from 0.1 g / 10 min to 10 g / 10 min, or from 0.5 g / 10 min to 8 g / 10 min, or from 0.5 g / 10 min to 5 g / 10 min.

[0077] In an embodiment, based on the gross weight of the oriented film, the ethylene-based polymer accounts for at least 50% by weight of the oriented film. All individual values ​​and subranges of at least 50% by weight are disclosed herein and include. For example, based on the gross weight of the oriented film, the ethylene-based polymer can account for at least 50% by weight, at least 75% by weight, at least 90% by weight, at least 99% by weight, or at least 99.9% by weight of the oriented film.

[0078] In addition to the ethylene-based polymer, in an embodiment, the oriented film may further include at least one additional polymer, and the at least one additional polymer may be selected from the group consisting of ultra low density polyethylene, low density polyethylene, polyethylene elastomer / plastomer, ethylene vinyl alcohol copolymer (EVOH), ethylene vinyl acetate, ethylene acrylic acid, or a combination thereof, in an amount less than 50 weight percent of the oriented film.

[0079] In an embodiment, the oriented film is a longitudinal oriented film. In such embodiments, the oriented film may be a polyethylene film of longitudinal orientation (MDO). In other embodiments, the oriented film is biaxially oriented. In such embodiments, the oriented film may be a biaxially oriented polyethylene (BOPE) film. In embodiments where the oriented film is BOPE, BOPE may be biaxially stretched using a tenter sequential biaxial stretching process, and may be referred to as a tenter biaxially stretched polyethylene (TF-BOPE). Such technology is generally known to those skilled in the art. In other embodiments, based on the teachings herein, other technologies known to those skilled in the art (such as a double bubble orientation process) may be used to biaxially orient the oriented film. Typically, a tenter sequential biaxial stretching process is used, and a tenter is incorporated as part of an extrusion line. After extrusion from a flat die, the film is cooled on a cooling roller and immersed in a water bath filled with room temperature water. The cast film is then transferred to a series of rollers with different rotational speeds to achieve stretching in the longitudinal direction. There are several pairs of rollers in the MD stretching section of the production line, and the several pairs of rollers are all oil heated. Pairs of rolls are used sequentially as preheating rolls, stretching rolls, and rolls for relaxation and annealing. The temperature of each pair of rolls is controlled individually. After stretching in the longitudinal direction, the film web is transferred to a tenter hot air oven with heating zones for stretching in the transverse direction. The first several zones are used for preheating, the following zones for stretching, and then the final zone for annealing.

[0080] The oriented film may also be a multilayer film or a monolayer film. For example, in an embodiment, the oriented film may be a monolayer TF-BOPE film comprising an ethylene-based polymer. In other embodiments, the oriented film is a multilayer film and includes at least two layers. For example, in an embodiment, the oriented film may be a multilayer TF-BOPE film comprising three layers (e.g., an A / B / C structure, which is a TF-BOPE film made by coextruding three layers using a single ethylene-based polymer resin). Embodiments of the oriented film may include, for example, a tie layer, a sealant layer, or a barrier layer. In an embodiment, the oriented film includes a barrier layer comprising an ethylene vinyl alcohol copolymer.

[0081] In an embodiment, the transverse stretch ratio of the oriented film is greater than its longitudinal stretch ratio, and the ratio of the percent elongation at break in the machine direction to the percent elongation at break in the cross direction of the oriented film is at least 2: 1. In an embodiment, the percent elongation at break of the oriented film in the machine direction may be at least 2 times greater than the percent elongation at break in the cross direction when measured according to ASTM D882, or in the alternative, at least 5 times greater, or in the alternative, at least 8 times greater, or in the alternative, at least 10 times greater.

[0082] In an embodiment, the oriented film is oriented in the longitudinal and / or transverse directions. In an embodiment, the oriented film may be stretched in the longitudinal direction at a stretch ratio of 2:1 to 6:1, or in the alternative at a stretch ratio of 3:1 to 5:1. In an embodiment, the oriented film may be stretched in the transverse direction at a stretch ratio of 2:1 to 9:1, or in the alternative at a stretch ratio of 3:1 to 8:1.

[0083] In embodiments, the oriented film may be corona treated, plasma treated, or printed using techniques known to those skilled in the art, either before or after lamination to the sealant film, depending on, for example, the end use application.

[0084] The multilayer films and oriented films disclosed herein can have various thicknesses, depending on, for example, the number of layers. For example, in embodiments, the multilayer film or oriented film can have a thickness of 10 to 200 microns, or alternatively 15 to 100 microns.

[0085] additive

[0086] It should be understood that any of the aforementioned layers of the multilayer film or oriented film may further include one or more additives known to those skilled in the art, such as antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, antistatic agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and foaming agents. For example, in an embodiment, the sealant layer of the multilayer film includes at least one of a slip agent or an antiblocking agent.

[0087] Laminate

[0088] As described above, the oriented film is heat laminated to the outer layers of the multilayer film, and the combination of the multilayer film and the oriented film provides the laminate.

[0089] The laminates of the present invention may have several desirable properties. For example, the laminates of the present invention may have one or more of the following properties: a bond strength of at least 2.00 N / 25 mm; a bond strength of less than 5.25 cm 3 / day / m 2 OTR; less than 5.75g / day / m 2 WVTR of less than 115°C at 5N; a seal strength of at least 4.0N / 25mm at 120°C; a hot tack initiation of less than 95°C at 1N; a hot tack strength of at least 1.20N at 110°C; and zero percent (0%) shrinkage at temperatures ranging from 70°C to 110°C.

[0090] In an embodiment, the laminate of the present invention may exhibit a bonding strength of at least 2.00 N / 25 mm, or alternatively at least 3.50 N / 25 mm, or at least 5.00 N / 25 mm, or at least 5.50 N / 25 mm, or at least 6.50 N / 25 mm, or at least 7.00 N / 25 mm, or at least 7.50 N / 25 mm, wherein the bonding strength may be measured according to the test method described below.

[0091] In embodiments, the laminates of the present invention may exhibit a thickness of less than 5.25 cm 3 / day / m 2 , or alternatively less than 4.00 cm 3 / day / m 2 , or alternatively less than 3.00 cm 3 / day / m 2 , or alternatively less than 2.50 cm 3 / day / m 2 OTR, where OTR can be measured according to the test method described below.

[0092] In embodiments, the laminates of the present invention may exhibit a relative humidity of less than 5.75 g / day / m 2 , or alternatively less than 5.00 g / day / m 2 , or alternatively less than 4.75 g / day / m 2 WVTR, wherein WVTR can be measured according to the test method described below.

[0093] In an embodiment, the laminate of the present invention may exhibit a heat seal initiation temperature at 5N of less than 115°C, or alternatively less than 110°C, or alternatively less than 105°C, or alternatively less than 95°C, or alternatively less than 85°C, or alternatively less than 75°C, wherein the heat seal initiation at 5N may be measured according to the test method described below.

[0094] In an embodiment, the laminate of the present invention may exhibit a seal strength at 120°C of at least 4.0 N / 25 mm, or alternatively at least 10.0 N / 25 mm, or alternatively at least 30.0 N / 25 mm, or alternatively at least 50.0 N / 25 mm, or alternatively at least 55.0 N / 25 mm, wherein the seal strength at 120°C may be measured according to the test method described below.

[0095] In an embodiment, the laminates of the present invention may exhibit a hot tack onset at 1 Newton of less than 95°C, or alternatively less than 80°C, or alternatively less than 78°C, or alternatively less than 76°C, or alternatively less than 72°C, wherein the hot tack onset at 1 Newton may be measured according to the test method described below.

[0096] In an embodiment, the laminate of the present invention may exhibit a hot tack strength at 110°C of at least 1.20N, or alternatively at least 1.60N, or alternatively at least 1.80N, or alternatively at least 4.00N, or at least 5.00N, wherein the hot tack strength may be measured according to the test method described below.

[0097] In an embodiment, the laminates of the present invention may exhibit zero percent (0%) shrinkage at 70°C, 80°C, 90°C, 100°C, and 110°C, wherein the shrinkage is measured according to the test method described below, and may provide a sealing window of 45°C or less, or alternatively 40°C or less, or alternatively 35°C or less.

[0098] In embodiments, the laminates of the present invention comprise at least 90 wt% polyethylene, or at least 95 wt% polyethylene, or at least 99 wt% polyethylene, or at least 99.5 wt% polyethylene, or at least 99.9 wt% polyethylene, based on the total weight of the laminate.

[0099] In embodiments, the laminates of the present invention are free of adhesives (eg, solvent-based adhesives or water-based adhesives).

[0100] Products

[0101] Embodiments of the present invention also provide articles formed by the laminates described herein. Examples of such articles may include packaging, flexible packaging, bags, and pouches. In some embodiments, the packaging of the present invention may contain liquids, powders, food, or other articles. In view of the teachings herein, the articles and packaging of the present invention may be formed by the laminates disclosed herein using techniques known to those skilled in the art in the art.

[0102] Test Method

[0103] density

[0104] Density is measured according to ASTM D792 and is expressed in grams / cm 3 (g / cm 3 )express.

[0105] Melt index (I2)

[0106] Melt index (I2) is measured according to ASTM D-1238 at 190°C and 2.16 kg. Values ​​are reported in g / 10 min, which corresponds to grams eluted per 10 min.

[0107] Oxygen Transmission Rate (OTR)

[0108] Oxygen transmission rate (OTR) was measured using Mocon Ox-Tran 2 / 21 according to ASTM D3985. The samples were dried at 23°C, 100% O2 gas, 0% RH, 50 cm 2 Sample size tested. Values ​​in cm 3 / day / m 2 Report.

[0109] Water Vapor Transmission Rate (WVTR)

[0110] Water vapor transmission rate (WVTR) was measured using Mocon Permatran-W 3 / 34 & 3 / 60 according to ASTM F1249. The samples were placed at 37.8°C, 100% RH, 50 cm 2 The sample size is tested. The value is expressed in g / day / m 2 Report.

[0111] Hot Tack Onset and Hot Tack Strength

[0112] Hot tack test was performed using J&B Hot Tack Tester 4000, with a sealing width of 25 mm, a dwell sealing time of 0.5 s, and a sealing pressure of 0.275 N / mm 2 (40 psi) and the hot tack pull speed was 200 mm / s. The hot tack onset is reported as the minimum temperature in degrees Celsius at which 1 Newton of force is reached. The hot tack strength is measured in units of Newtons / 25 mm (N / 25 mm).

[0113] Heat seal initiation temperature and seal strength

[0114] To determine the heat seal initiation temperature (HSIT) and seal strength, the samples were sealed by a J&B Hot Tack 4000 tester. The sample width was 25 mm, the dwell seal time was 0.5 seconds and the sealing pressure was 0.275 N / mm 2 The heat sealed samples were conditioned for 24 hours and then measured using a Zwick tensile machine equipped with a 200N load cell and a tensile speed of 500mm / min. HSIT is reported as the minimum temperature in degrees Celsius at which 5 Newtons of force are reached. Seal strength is reported in N / 25mm.

[0115] Shrinkage

[0116] Shrinkage (%) is obtained by measuring the length and width of the seal area in the machine direction (MD) and transverse direction (TD) after the films are heat sealed together and calculating the percentage change compared to the seal strip width, which can be between 1 mm and 15 mm. Standard heat sealers (including PULSA impulse sealers or J&B heat seal testers) can be used if they have accurate and adjustable temperature controllers. Sealing conditions include jaw pressure (40-80 psi or 0.275-0.552 N / mm 2 ), dwell time (0.1-1.5 seconds) and sealing temperature (60-150°C) windows, and depends on the packaging speed, where a typical condition for a high-speed packaging machine is a jaw pressure of 40 psi (0.275 N / mm 2 ), the dwell time is 0.5 seconds.

[0117] Adhesion strength

[0118] The bond strength is measured with a Zwick tensile tester at a pulling speed of 250 mm / min and with a 25 mm wide strip. The tensile tester is equipped with a fixture (sample holding T-shaped) for fixing the ends of a partially delaminated or partially peeled sample before being pulled apart. The upper fixture connected to the crosshead is driven in the tensile direction to measure the force or bond strength required between two adjacent layers of a multilayer sample. The maximum force and average force results are calculated from 5 measurements and are recorded in Newtons (N / 25 mm strip).

[0119] Maximum peak melting temperature (Tm)

[0120] Differential scanning calorimetry (DSC) is used to measure the melting and crystallization behavior of polymers over a wide temperature range. For example, a TA Instruments Q1000 DSC equipped with an RCS (refrigerated cooling system) and an autosampler is used to perform this analysis. The instrument is first calibrated using the software calibration wizard. First, a baseline is obtained by heating a single cell from -80°C to 280°C without any sample in the DSC aluminum dish. Then a sapphire standard is used as instructed by the calibration wizard. Next, a fresh indium sample of 1 to 2 milligrams (mg) is analyzed by heating the standard sample to 180°C, cooling to 120°C at a cooling rate of 10°C / min, and then isothermally holding the standard sample at 120°C for 1 minute. The standard sample is then heated from 120°C to 180°C at a heating rate of 10°C / min. Then, it is determined that the indium standard sample has a heat of fusion (H f ) = 28.71 ± 0.50 Joule / gram (J / g) and initial melt temperature = 156.6° C. ± 0.5° C. The test sample was then analyzed on a DSC instrument.

[0121] During the test, a nitrogen purge gas flow of 50 ml / min was used. Each sample was melt pressed into a film at about 175°C; the molten sample was then air cooled to room temperature (about 25°C). The film samples were formed by extruding a "0.1 gram to 0.2 gram" sample at 175°C, 1,500 psi for 30 seconds to form a "0.1 mil to 0.2 mil thick" film. A 3 mg-10 mg, 6 mm diameter sample was extracted from the cooled polymer, weighed, placed in a light aluminum pan (about 50 mg), and sealed with a gland. Analysis was then performed to determine its thermal properties.

[0122] The thermal behavior of the sample is determined by ramping up and down the sample temperature to produce a heat flow versus temperature curve. First, the sample is quickly heated to 180°C and isothermally held for five minutes to remove its thermal history. Next, the sample is cooled to -40°C at a cooling rate of 10°C / minute and isothermally held at -40°C for five minutes. The sample is then heated to 150°C at a heating rate of 10°C / minute (this is the "second heating" ramp). The cooling curve and the second heating curve are recorded. The cooling curve is analyzed by setting a baseline endpoint from the start of crystallization to -20°C. The heating curve is analyzed by setting a baseline endpoint from -20°C to the end of melting. The measured value is the highest peak melting temperature (T m ), the highest peak crystallization temperature (T c ), initial crystallization temperature (T c The calculated crystallinity of the polyethylene samples was calculated using the following formula: % crystallinity of PE = ((Hf) / (292 J / g)) × 100, and the calculated crystallinity of the polypropylene samples was calculated using the following formula: % crystallinity of PP = ((Hf) / 165 J / g)) × 100. The heat of fusion (Hf) is reported from the second thermal curve. f ) and the highest peak melting temperature. The highest peak crystallization temperature and the onset crystallization temperature are determined based on the cooling curve.

[0123] Example

[0124] The following examples illustrate features of the present disclosure but are not intended to limit the scope of the present disclosure.

[0125] Polymer / Membrane used

[0126] The following materials are included in the example laminates discussed below.

[0127] ELITE TM 5960G1 is a reinforced polyethylene resin with a density of 0.962g / cm 3And has a melt index (I2) of 0.85 g / 10 min., and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0128] DOW TM LDPE 450E is a low-density polyethylene with a density of 0.923 g / cm 3 and has a melt index (I2) of 2.0 g / 10 min. and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0129] BYNEL TM 22E780 is a polyethylene / acrylate copolymer resin with a density of 0.94 g / cm 3 and has a melt index (I2) of 2 g / 10 min. and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0130] ELVAX TM 470 is an ethylene vinyl acetate copolymer having 18 wt% vinyl acetate comonomer content and a density of 0.941 g / cm 3 And has a melt index (I2) of 0.7 g / 10 min., and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0131] BYNEL TM 41E710 is a linear low-density polyethylene with a density of 0.922 g / cm 3 And has a melt index (I2) of 2.7 g / 10 min., and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0132] EVAL TM H171B is a 38 mol% ethylene vinyl alcohol copolymer with a density of 1.17 g / cm 3 And the melt index (I2) is 1.7 g / 10 min, and is commercially available from Kuraray Co., Ltd. (Tokyo, Japan).

[0133] SURLYN TM 1707 is an ionomer of ethylene acid copolymer neutralized with a sodium cation source and has a maximum peak melting temperature (T m ) is 92°C and has a density of 0.95 g / cm 3 And has a melt index (I2) of 0.9 g / 10 min., and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0134] AFFINITY TM PF 7266 is a polyethylene elastomer / plastomer with a peak melting temperature (T m) is 76°C and the density is 0.885 g / cm 3 And has a melt index (I2) of 2.5 g / 10 min., and is commercially available from The Dow Chemical Company, Midland, Michigan.

[0135] ADCOTE TM Dow® 545S / Co-reactant F is a solvent based, 2-component polyurethane adhesive commercially available from The Dow Chemical Company, Midland, Michigan.

[0136] CE505 is a slip masterbatch commercially available from Lyondell Basell (Houston, TX).

[0137] AB5 is an antiblock masterbatch commercially available from LyondellBasell, Houston, TX.

[0138] CONPOL TM 13B is an antiblock masterbatch commercially available from The Dow Chemical Company, Midland, Michigan.

[0139] CONPOL TM 20S1 is a slip masterbatch commercially available from The Dow Chemical Company, Midland, Michigan.

[0140] TF-BOPE film is a biaxially oriented film of linear low-density polyethylene, which is stretched to a thickness of 20 microns by a tentering machine at a stretch ratio of 3-5X in the longitudinal direction and 7-9X in the transverse direction. The density of linear low-density polyethylene is 0.926 g / cm 3 and a melt index (I2) of 1.7 g / 10 min. and is available from The Dow Chemical Company (Midland, Michigan) under the name INNATE TM XUS 59910.08 was commercially available.

[0141] BOPP film is a printed biaxially oriented film processed at 36 dynes and has an 18 micron gauge.

[0142] The laminates designated as Inventive Examples 1-5 and Comparative Examples 1-2 were formed in a PRINT-ABCBD configuration, where "PRINT" corresponds to the TF-BOPE films of the Inventive Examples and the BOPP films of the Comparative Examples (oriented films) and "ABCBD" corresponds to the five-layer multilayer coextruded films (multilayer films). For each Inventive Example, the TF-BOPE film was heat laminated to the five-layer multilayer film using a hot roll lamination process performed on a ChemInstruments #007416 at a temperature of 160°C, a pressure of 60 psi, and a speed of 0.75 m / min. The examples were conditioned and cured for 24 hours. For each Comparative Example, ADCOTE was applied at a coating weight of 3 gsm-3.5 gsm using TM 545S / Co-reactant F BOPP film was laminated to a five layer multilayer film. The examples were cured at room temperature (25°C) for two days and subjected to a hot roll lamination process on a ChemInstruments #007416 at 75°C temperature, 60 psi pressure and 1.66 m / min speed.

[0143] The five-layer multilayer coextruded film for each of the present embodiments and comparative examples was formed on a Collin 5-layer blown coextrusion line with the following parameters: target film thickness: 55 μm; extrudate: 4 extruders; layer configuration: A / B / C / B / D; layer ratio (%): 18.2% / 13.6% / 18.2% / 13.6% / 36.4% (or 2 / 1.5 / 2 / 1.5 / 4); layer thickness (μm): 10 / 7.5 / 10 / 7.5 / 20; die diameter (mm): 50; blow molding ratio (BUR): 3.0; wiring width: 235 mm; total throughput of 8 kg / h; line speed of 5.4 m / min; melt temperatures (°C) of extruders A, B, C and D were 163-174°C, 191°C, 195°C and 175-185°C.

[0144] Table 1 below provides the structures and compositions of the laminate examples, inventive examples 1-5, and comparative examples 1-2.

[0145] Table 1 - Laminate structure and composition

[0146]

[0147]

[0148] *Except 80% AFFINITY TM PF 7266, except for D layer, contains 10% CE505 and 10% AB5.

[0149] **Except 93.5% SURLYN TM 1707, D layer contains 4% CONPOL TM 13B and 2.5% CONPOL TM 20S1.

[0150] The thickness, oxygen permeability (OTR), water vapor permeability (WVTR) and bonding strength of the examples were measured. Table 2 provides the results. As shown in Table 2, the bonding strength of the examples of the present invention is surprisingly high compared to the bonding strength of the comparative examples. Although there is no laminating adhesive in the laminate, there is no delamination between the multilayer film and the oriented film in the examples of the present invention. Although the comparative examples in various aspects show lower OTR and WVTR values, the comparative examples are incompatible with polyethylene recycling streams. In addition, it will be understood by those of ordinary skill in the art that the OTR of the laminate can be adjusted according to the thickness of the barrier layer and the ethylene content of the EVOH (i.e., generally, the thicker the barrier layer or the lower the ethylene content, the lower the achievable OTR value). As described above, the examples of the present invention are non-limiting examples and are not intended to limit the scope of the present disclosure, and the multilayer film according to an embodiment of the present invention may include a barrier layer comprising EVOH having an ethylene content of 20 mol% to 50 mol%.

[0151] Table 2 - Thickness Bond Strength, OTR and WVTR

[0152]

[0153] *The BOPP film used for the comparative example was a printed BOPP in which the printed ink side was laminated to a five-layer film using a solvent-based lamination adhesive, and therefore the bonding strength was measured from the printed ink side of the BOPP to the five-layer film.

[0154] Heat seal initiation temperature (HSIT), heat seal strength, hot tack initiation temperature at 1 Newton and hot tack strength were measured. Figure 1 Heat seal strength curves of Comparative Example 1 and Inventive Examples 1-3 are shown. Figure 2 The hot tack strength curves of Comparative Example 2 and Inventive Examples 4-5 are shown. Table 3 provides the results of Comparative Example 1 and Inventive Examples 1-3, where AFFINITY TM PF 7266 is part of the sealant layer / layer D. From the data in Table 3, the inventive examples have lower HSIT and higher seal strength in all aspects. Table 4 provides the results of Comparative Example 2 and Inventive Examples 4-5, where SURLYN TM1707 is part of the sealant layer / layer D. From the data in Table 4, the present invention examples show higher or desired hot tack strength. According to Tables 3 and 4, the present invention examples show desired or maintained low hot tack initiation temperature and low HSIT. The present invention examples also achieve in terms of desired, maintained or improved seal strength performance.

[0155] Table 3 - HSIT, seal strength, hot tack onset and hot tack strength of Comparative Example 1 and Inventive Examples 1-3 .

[0156]

[0157]

[0158] Table 4 - HSIT, seal strength, hot tack onset and hot tack strength of Comparative Example 2 and Inventive Examples 4-5 .

[0159]

[0160] The shrinkage (%) of the Examples was measured at 70°C, 80°C, 90°C, 100°C, 110°C, and 120°C. No Example showed shrinkage at 70°C, 80°C, 90°C, 100°C, or 110°C in the machine direction (MD) or transverse direction (TD). The shrinkage results (%) of the Examples are reported in Table 5. Although the Examples of the present invention showed some shrinkage at 120°C compared to the Comparative Examples, the Examples of the present invention can perform equivalent to or similar to the Comparative Examples in a lower temperature range of about 70°C-110°C, which provides a wide sealing window of at least 40°C.

[0161] Table 5 - Shrinkage (%) within the heat seal window between 70°C and 120°C

[0162]

[0163]

[0164] * Sealing strip size: 0.5cm (MD direction) X 2.5cm (TD direction).

[0165] Unless expressly excluded or otherwise limited, each document cited herein, if any, including any cross-referenced or related patents or applications to which this application claims priority or rights, and any patent applications or patents, is hereby incorporated by reference in their entirety. The citation of any document does not admit that it is prior art to any invention disclosed or claimed herein, or that it alone or in combination with any other reference or more than one reference teaches, suggests or discloses any such invention. In addition, in the event that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to the term in this document shall prevail.

[0166] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.

Claims

1. A laminate comprising: (a) A multilayer film comprising: (1) an outer layer, the outer layer comprising at least one of the following: anhydride-modified ethylene acrylate copolymer, anhydride-modified polyethylene, anhydride-modified ethylene vinyl acetate, ethylene-vinyl acetate copolymer, ethylene-ethylene acrylic acid copolymer, ethylene-acrylate copolymer, or polyethylene elastomer or plastomer; (2) a barrier layer comprising ethylene vinyl alcohol copolymer; (3) A sealant layer, wherein the sealant layer comprises at least 70% by weight of a highest peak melting temperature T m A polymer having a temperature of 108°C or less; and (4) a tie layer, the tie layer being located between the barrier layer and the sealant layer, wherein the tie layer comprises anhydride-modified linear low-density polyethylene and at least one of the following: linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, or high-density polyethylene; and (b) an oriented film thermally laminated to the outer layer of the multilayer film and comprising a density of 0.900 g / cm 3 Up to 0.970g / cm 3 The ethylene-based polymer, wherein the oriented film is a biaxially oriented polyethylene (BOPE) film.

2. The laminate of claim 1, wherein the multilayer film further comprises a second tie layer between the outer layer and the barrier layer.

3. The laminate of claim 1 or 2, wherein the barrier layer is 5% to 25% of the total thickness of the multilayer film.

4. The laminate of claim 1 or 2, wherein the sealant layer is at least 10 microns thick.

5. The laminate of claim 1 or 2, wherein the sealant layer is 25% to 60% of the total thickness of the multilayer film.

6. The laminate of claim 1 or 2, wherein the oriented film comprises a barrier layer comprising ethylene vinyl alcohol copolymer.

7. The laminate of claim 1 or 2, wherein the sealant layer comprises a polyethylene elastomer or plastomer.

8. The laminate of claim 1 or 2, wherein the sealant layer comprises an ionomer of an ethylene acid copolymer.

9. The laminate of claim 1 or 2, wherein the outer layer further comprises at least one of the following: linear low density polyethylene, low density polyethylene, medium density polyethylene, or high density polyethylene.

Citation Information

Patent Citations

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Interpolymers of ethylene and unsaturated carboxylic acids

    US4599392A

  • Elastic substantially linear olefin polymers

    US5272236A